2011
DOI: 10.1097/rhu.0b013e318204a8f9
|View full text |Cite
|
Sign up to set email alerts
|

The Experience and Impact of Living With Gout

Abstract: Chronic gout has an important impact on both the patient and his family. This work provides previously hidden perspectives of the experience of gout, which may be generalized to other men with gout, suggesting that shame, embarrassment, and stigma lead to trivialization of the impact of disease despite its severity. These experiences may lead to undertreatment of gout because of lack of disclosure of symptom severity and lack of expectation of treatment effectiveness, which in turn could contribute to the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 17 publications
8
57
3
Order By: Relevance
“…Patients also needed crutches and walking aids during acute gout flares and felt that they were aging prematurely. Our study confirmed the impact of gout on patients’ lives recognized in the earlier study [26], namely, severe pain, dependency, work disability, dietary restrictions and social isolation. These findings substantiate the disease burden and the broad impact on patients’ lives.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Patients also needed crutches and walking aids during acute gout flares and felt that they were aging prematurely. Our study confirmed the impact of gout on patients’ lives recognized in the earlier study [26], namely, severe pain, dependency, work disability, dietary restrictions and social isolation. These findings substantiate the disease burden and the broad impact on patients’ lives.…”
Section: Discussionsupporting
confidence: 91%
“…The concept covered was broad and diverse and women were not included. Our study builds on this foundation [26] and adds significant knowledge to this area. Other qualitative and quantitative studies have covered an even wider range of gout-related issues including treatment, knowledge, disease monitoring, outcomes and patient and clinician perspective within each study [24,25,42].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As a result, patients known to have gout are often reluctant to seek help for fear that they will not be taken seriously or will be blamed for their lifestyle habits,1416 meaning that practitioners are often unaware that patients have troublesome symptoms. When patients develop gout, they are frequently given inaccurate or conflicting information which trivialises gout and misrepresents its causes and treatment 1214.…”
mentioning
confidence: 99%